Synthesis and Characterization of Copper-Iron Nitride Thin Films. Issue 3 (2016) - Kamat, Hrishikesh; Wang, Xingwu; Parry, James; Qin, Yueling; Zeng, Hao
ABSTRACT: Iron nitride thin films have potential applications in the biomedicine and energy. The magnetic properties of these films can be tuned by incorporating copper nitride. In this study, iron copper nitride thin films have been fabricated by magnetron sputtering technique either by co-sputtering iron nitride and copper nitride or by layer stacking of the materials. The structure, morphology and magnetic properties of the films have been studied by scanning electron microscopy, x-ray diffraction, x-ray reflectivity and vibrating sample magnetometry.